Applying Standards of Effectiveness to Noncontingent Reinforcement: A Systematic Literature Review. Issue 4 (July 2021) - Meindl, James N.; Ivy, Jonathan W.; Glodowski, Kathryn R.; Noordin, Komal
Noncontingent reinforcement is a time-based schedule of reinforcement that has been shown to decrease problem behavior. Although the intervention is considered well established, there exist concerns that much of the supporting research has been conducted under highly controlled experimental conditions that may lack ecological validity. That is, although the efficacy has been demonstrated, the effectiveness in less controlled settings has not. To evaluate this concern, we analyzed research on noncontingent reinforcement between 1993 and 2017. Standards of evidence for effectiveness were adapted from prevention science and applied to noncontingent reinforcement literature. We specifically focused on generalizability across populations and settings, the conditions under which the intervention was applied, specific treatment parameters, opportunity cost, and social validity. Our results indicate several areas where evidence of noncontingent reinforcement effectiveness in applied settings is limited. We identify these limitations and provide a range of recommendations for future research to promote more widespread dissemination of the procedure.